HAEMATOCOCCUS PLUVIALIS MODULATING EFFECT ON NEUROTRANSMITTERS, HORMONES AND OXIDATIVE DAMAGE-ASSOCIATED WITH ALZHEIMERÂ´S DISEASE IN EXPERIMENTAL RATÂ´S MODEL - El-baz, Farouk K.; Aly, Hanan F.; Ali, Gamila H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study was planned to assess the efficacy of Haematococcus pluvialis in the regression of Alzheimer's disease (AD). Methods: Fifty rats were divided into five groups. Positive control group orally received aluminium chloride in a dose 100 mg/kg to induce AD: AD induced rats were orally treated with H. pluvialis extract (150 mg/kg) and rivastigmine standard drug (4.6 mg/kg/day) for 30 d. Brain acetylcholine esterase (AchE), acetylcholine (Ach), dopamine (DA), adrenaline (A), noradrenaline (NA), oxidative stress biomarkers and superoxide dismutase (SOD) were determined. Further, adrenocorticotropic hormone (ACTH) and cortisol (CORT) levels were evaluated. Also, brain histopathological investigation was examined. Results: AD induced rats recorded a significant increase in the brain AchE, concomitant with a significant decrease in Ach, DA, NA, A and SOD levels. While, a significant increase in NO and H2O2, CORT and ACTH was recorded. Moreover, brain histopathological investigation in AD rats showed the formation of amyloid plaques and necrosis of neurons. Treatment of AD induced rats with extract of H. pluvialis or standard drug resulted in an improvement in the most of the all studied biochemical parameters. Also, AD groups treated with extract or standard drug showed great improvement in the brain morphological structure with normalisation of cerebral cortex and hippocampus, though, necrosis of some cerebral neurones was detected. Conclusion: This current study indicated that H. pluvialis extract and drug significantly ameliorates the neurotransmitters level, oxidative damage as well as pituitary function due to their anticholinesterase activity, antioxidant efficacy, beside the anti-inflammatory effect.